The Effect of Student Facilitator Model and Explaining towards Students' Learning Competencies in Global Warming Material at Junior High School 4 Koto XI Tarusan - Mawarni Rezki; Siska Alicia Farma; Sa'diatul Fuadiyah; Lufri Lufri (Universitas Negeri Padang, 2019)
This research aims to find out the effect of Student Facilitator and Explaining model towards students' learning competencies, which still below from the average and there have no learning process that pursue the students to be active and creative until the students can increase their learning competencies; both cognitive and affective rather for students psikimotor in learning process. The research was quasi-experimental reserach with randomize control group post-test only design. The sample was taken by purposive sampling technique which grade VII.3 as the experimental group and garde VII.4 as the control group. The population of this research was VII grade students that devided into seven classes at SMPN 4 Koto XI Tarusan in academic year 2018/2019. The result of this research showed the average score for grade VII.3 was (77,15) for experimental group and (68,52) for control group in students' learning competency. Then for behavioural competence the average score in experimental group was (84,08) and the control group reached (78,96) which the data was distributed normally and variant homogeneously. In hyphotesis testing was found by the formula tcount> ttable, learning competency (2,73 > 1,68), behavioural competency (2,77 > 1,68). Based on the result of the study, it can be concluded that the Student Facilitator and Explaining model give positive effect for the students' learning competency in global warming material at SMPN 4 Koto XI Tarusan.